KELAYAKAN FILM DOKUMENTER SUBMATERI MANFAAT KEANEKARAGAMAN HAYATI KELAS X - Sepsamli, Letus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Â  Abstract This research was aimed to found out the feasibility of submaterial media documentary film of biodiversity benefits for X grade senior high school. The method that was used in this research was a descriptive method purposive sampling. It was evaluated for its feasibility by material and media experts. The material experts was a lecturer of Biology Education Study Program of Teacher Training and Education Faculty of Tanjungpura University, a biology teacher of one of senior high school in Pontianak, and a biology teacher on tenth grade senior high school in Landak regency. Then, the media experts was a lecturer of Biology Education Study Program of Teacher Training and Education Faculty of Tanjungpura University and two ICT teachers of senior high school in Landak Regency. According to the assessment that was given by the validators, documentary film belongs to the valid category as a learning material with the average score of total validation was 3,68 and valid category as a learning media with the average score of total validation was 3,6 and suitable to be used as a learning media. According to the average score of total validation, documentary film suitable to be used as a learning media. Keywords: Biodiversity, Media, Documentary film